2017
DOI: 10.1039/c6cp07654h
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of gas adsorption for pristine, defective and functionalized graphene

Abstract: Defect is no longer deemed an adverse aspect of graphene. Contrarily, it can pave ways of extending applicability of graphene. Here, we discuss the effects of three types of defects on graphene: carbon deficiency, adatom (single Fe) dopant and introduction of functional groups (carboxyl, pyran group) on NO 2 gas adsorption via density functional theory method. We have observed that the unsaturated carbon in defected graphene is highly active to attract NO 2 molecules. Our study suggests that introducing Fe on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(41 citation statements)
references
References 42 publications
0
36
1
4
Order By: Relevance
“…In this regard, introducing defects (mono-vacancies and vacancy complexes) into graphene-family materials can be an effective tool to enhance the adsorption ability of heavy metals, thereby avoiding surface functionalization/immobilization steps. Recently, it has been demonstrated that the defect-engineering approach in the case of graphene can promote the increase of the binding energy of alkaline-earth metals and hydrogen, 60 gas molecules and water, 61,62 Li, 63 Pt, 64 Cd, 65 Co 66 and 3d transition metals (from Sc to Zn). 67 Nevertheless, there is still a limited amount of data in the literature on the role of vacancy-related defects in the complexation between elemental toxic heavy metals and graphene-like structures.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, introducing defects (mono-vacancies and vacancy complexes) into graphene-family materials can be an effective tool to enhance the adsorption ability of heavy metals, thereby avoiding surface functionalization/immobilization steps. Recently, it has been demonstrated that the defect-engineering approach in the case of graphene can promote the increase of the binding energy of alkaline-earth metals and hydrogen, 60 gas molecules and water, 61,62 Li, 63 Pt, 64 Cd, 65 Co 66 and 3d transition metals (from Sc to Zn). 67 Nevertheless, there is still a limited amount of data in the literature on the role of vacancy-related defects in the complexation between elemental toxic heavy metals and graphene-like structures.…”
Section: Introductionmentioning
confidence: 99%
“…Настоящая работа посвящена исследованию адсорбции радикалов H, O, OH, COOH на растянутый N-легированный графен. Перечисленные радикалы являются распространенными адсорбатами: H интересен с точки зрения запасания водорода [27]; O и OH играют важную роль при приготовлении, очистке и функционализации графена [28][29][30][31]; OH и COOH обеспечивают его биосовместимость [32][33][34], COOH улучшает его адсорбционные свойства [35,36]. Механическое растяжение существенно меняет не только электронные [37], оптические [38] и термические [39,40] свойства графена, но и его химическую активность [41].…”
Section: Introductionunclassified
“…[2][3][4] и ссылки, приведенные там). Выяснилось, что адсорбция сопровождается сравнительно малым пере-ходом заряда между адсорбентом и адсорбатом.…”
unclassified
“…Выяснилось, что адсорбция сопровождается сравнительно малым пере-ходом заряда между адсорбентом и адсорбатом. При этом, например, NO 2 и Н 2 О действуют как акцепторы, тогда как NH 3 , CO и NO являются донорами. Переход заряда имеет место как для собственного (идеального) графена, когда связь адмолекула−графен является слабой (близкой к ван-дер-ваальсовой), так и для графена, допированного и/или содержащего структурные дефекты.…”
unclassified
See 1 more Smart Citation